PENDUGAAN POPULASI BEKANTAN (Nasalis larvatus) DI TAMAN WISATA ALAM TANJUNG BELIMBING KECAMATAN PALOH KABUPATEN SAMBAS - Selpa, Selpa; Rifanjani, Slamet; muflihati, muflihati (JURNAL HUTAN LESTARI, 2019)
Proboscis monkey (Nasalis larvatus) is an endemic animal of Borneo including protected primate species as an endangered species status. This species listed as an endangered species caused by large population decline and habitat demage continues to threaten the proboscis population. This research was conducted in Taman Wisata Alam Tanjung Belimbing (TWATB) is a nature conservation area that supports the conservation of proboscis monkey. The purpose of this research is to collect the amount of proboscis monkey populations, so as to provide an overview of conservation efforts that must be carried out. The method was used the River Survey method. The result of Proboscis research based on the age level was found consisted average of 5 adult male individuals, 6 adult female individuals, 7 adolescent individuals and 5 childs. Estimation of the population is calculated using the King’s Method. Estimated individuals population is 12 individuals with a density of 25.5 individuals/km2.Keywords: Proboscis monkey, Population, Tanjung Belimbing, Paloh.